GENDER INEQUALITY IN THE CRIMINAL JUSTICE SYSTEM: A CASE STUDY OF HANDLING CASES OF VIOLENCE AGAINST WOMEN - Yulia Bakri; Agus Prihartono Permana Sidik (Catalist Indo Publisher, 2026)
This study aims to analyze gender inequality in the criminal justice system, particularly in the handling of cases of violence against women. The research method used is a case study with a qualitative approach, involving the analysis of legal documents, court decisions, and in-depth interviews with various related parties such as victims, law enforcement officials, and legal experts. The results of the study show various forms of gender inequality, ranging from bias in legal interpretation, lack of victim perspective, to stigma and discrimination against women in the judicial process. The implementation of Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) is expected to be a progressive step in providing more comprehensive legal protection for victims, but challenges in law enforcement remain a major concern. This study also highlights the importance of reconstructing the model of judicial decisions with a progressive legal approachas well as strengthening the criminal justice system specifically for women victims of violence. The study's conclusions emphasize the need for fundamental changes in the criminal justice system to ensure gender justice, including enhancing the capacity of law enforcement officials, changing legal culture, and ensuring active victim participation in the judicial process.